Konsep Wasaṭiyyah dalam Tafsīr al-Manār dan Relevansinya Terhadap Tantangan Ekstremisme Keagamaan Kontemporer - Ulul Azmi; Sukiman Sukiman; Husnel Anwar Matondang (Kamaya: Jurnal Ilmu Agama, 2025)
The concept of wasaṭiyyah in Islam is a central issue relevant in responding to contemporary religious extremism phenomena such as radicalism, intolerance, and religion-based violence. Muḥammad ‘Abduh’s Tafsīr al-Manār, continued by Rasyīd Riḍā, presents rational-reformist thinking that emphasizes balance, justice, and openness, so that it can be positioned as a theoretical and practical framework for understanding Islamic moderation. This study aims to examine the idea of ​​wasaṭiyyah in Tafsīr al-Manār and outline its contribution to addressing contemporary religious extremism. The method used is a qualitative approach with a literature study approach through content analysis of the tafsir text and related literature. The results of this study indicate that the concept of wasaṭiyyah in Tafsīr al-Manār is built on three foundations: a rational understanding of the revealed text while taking into account the social context, an emphasis on social justice and human brotherhood, and a rejection of both excessive attitudes (ifrāṭ) and neglect (tafrīṭ) in religion. The relevance of this concept is evident in its ability to correct the ideology of takfir, encourage interfaith dialogue, strengthen national commitment, and affirm Islam as a religion that aligns with universal humanitarian values. This study contributes by offering a new perspective on interpretation-based counter-extremism, which makes wasaṭiyyah not only a theological idea, but also a strategic, practical paradigm in affirming Islamic moderation amidst global challenges.